Platelets mediate cytotoxic T lymphocyte–induced liver damage - Iannacone, Matteo (2005)
We found that platelet depletion reduces intrahepatic accumulation of virus-specific cytotoxic T lymphocytes (CTLs) and organ damage in mouse models of acute viral hepatitis. Transfusion of normal but not activation-blocked platelets in platelet-depleted mice restored accumulation of CTLs and severity of disease. In contrast, anticoagulant treatment that prevented intrahepatic fibrin deposition without reducing platelet counts did not avert liver injury. Thus, activated platelets contribute to CTL-mediated liver immunopathology independently of procoagulant function.